2018
DOI: 10.1016/j.bmcl.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and evaluation of l-cystine diamides as l-cystine crystallization inhibitors for cystinuria

Abstract: To overcome the chemical and metabolic stability issues of l-cystine dimethyl ester (CDME) and l-cystine methyl ester (CME), a series of l-cystine diamides with or without N-methylation was designed, synthesized, and evaluated for their inhibitory activity of l-cystine crystallization. l-Cystine diamides 2a-i without N-methylation were found to be potent inhibitors of l-cystine crystallization while N-methylation of l-cystine diamides resulted in derivatives 3b-i devoid of any inhibitory activity of l-cystine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…To overcome the chemical and metabolic stability issues of L-CDME and L-CME, a series of l-cystine diamides with or without Nα-methylation was designed, synthesized, and evaluated for their inhibitory activity of l-cystine crystallization. Among the l-cystine diamides 2a-i, l-cystine bismorpholide (CDMOR, LH707, 2g) and l-cystine bis(N'-methylpiperazide) (CDNMP, LH708, 2h) are the most potent inhibitors of l-cystine crystallization (67).…”
Section: Bucillaminementioning
confidence: 99%
“…To overcome the chemical and metabolic stability issues of L-CDME and L-CME, a series of l-cystine diamides with or without Nα-methylation was designed, synthesized, and evaluated for their inhibitory activity of l-cystine crystallization. Among the l-cystine diamides 2a-i, l-cystine bismorpholide (CDMOR, LH707, 2g) and l-cystine bis(N'-methylpiperazide) (CDNMP, LH708, 2h) are the most potent inhibitors of l-cystine crystallization (67).…”
Section: Bucillaminementioning
confidence: 99%
“…Measurements of residual l -cystine concentrations in solution after crystallization using a fluorescent tag protocol during bulk crystal growth revealed substantial differences (Figure B) among the inhibitors. , Here, the concentration effect of an inhibitor that elevates the supersaturation of l -cystine following crystallization is benchmarked using EC 2 x , the inhibitor concentration corresponding to an l -cystine concentration twice that of the lower plateau. l -CDMOR and l -CDNMP were superior to l -CDME with significantly lower EC 2 x values, corresponding to higher supersaturations and suggesting more effective kinetic inhibition of l -cystine growth compared to l -CDME.…”
Section: Molecular Imposters and Growth Inhibitionmentioning
confidence: 99%
“…The stereochemical specificity of molecular imposter binding to crystal sites was tested by measuring step velocities in the presence of various molecules from a library of more than 50 compounds (some examples are shown in Figure ). , This library included molecules in which the terminal hydroxyl group of l -cystine was replaced or its backbone core was modified as well as compounds based on l -cysteine. The step velocity measurements revealed that the most effective inhibitors were l -cystine diesters and diamides that retained the essential structural elements of cystine.…”
Section: Molecular Imposters and Growth Inhibitionmentioning
confidence: 99%
“…A series of diamines, which mimic cystine and interfere with its crystallization, have shown efficacy in vitro and in a knockout mouse model. [40][41][42] The effect of these molecules is attributed to steric hindrance, where side chains prevent additional molecules of cystine from being added to crystals. No studies of these drugs in humans with cystinuria have been performed as of yet.…”
Section: Future Directionsmentioning
confidence: 99%